Religion and charity: the social life of goodness in Chinese societies - Weller, Robert P. (Cambridge University Press, 2018)
Engaged religions and the social life of goodness -- Legacies and discontinuities in China, Taiwan and Malaysia -- Political merit-making: religious philanthropy and the state -- A (Chinese) good person -- Gifts, groups, and goodness -- Innovating the good -- Alternative goodness